Complementary and alternative medicine legitimation efforts in a hostile environment: The case of Portugal - Bicho, M.; Nikolaeva, R.; Lages, C. (Sociology of Health and Illness, 2023)
This article explores complementary and alternative medicine (CAM) organisations’ legitimation efforts that face extra obstacles as they are subject to more than one institutional logics (hybrids) and operate in a contested organisational space (hostile environment). CAM organisations espouse the health and market logics and their practices are questioned at an institutional level. The study is conducted in Portugal, where the legali-sation of CAM therapies was a contested process over 10 years. Taking an abductive approach and drawing on qualitative interviews, the authors analyse CAM manag-ers’ efforts to legitimise their practices and build viable organisations despite hostile conditions. Contrary to prior studies of hybrid healthcare organisations, CAM organisations derive moral legitimacy from the market logic rather than the health logic. The findings show that relationships, trust-building and consumer educa-tion appear to be the primary vehicles for establishing pragmatic legitimacy. Thus, pragmatic legitimacy relies on the health logic. The market logic dominates the pursuit of moral legitimacy through financial sustain-ability, human capital, marketing communications and partnerships, and advocating complementarity with biomedicine. We propose a model through which organ-isations use pragmatic legitimacy to enhance moral legitimacy and to create recursive feedback between moral and pragmatic legitimacy on the path to cognitive legitimacy.